PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENGASAH KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK PADA SUB MATERI FAKTOR FAKTOR YANG MEMPENGARUHI LAJU REAKSI KELAS XI SMA NEGERI 2 BANGKALAN (Universitas Negeri Surabaya, 2020)
The aims of this research is to determine students’ critical thinking skills through implementation of guided inquiry learning models in sub matter factors that affect reaction rate including the syntax implementation of guided inquiry learning models, student activities, students’ critical thinking skills, and cognitive learning outcomes. This research was conducted in SMA Negeri 2 Bangkalan using the One Group Pretest Posttest Design to determine student’s critical thinking skills and One Shot Case Study to determine students’ cognitive learning outcomes. The data obtained were analyzed using quantitative analysis methods. It can be concluded that (1) Syntax implementation of the guided inquiry learning model at 3 meetings shows the average percentages at meetings 1, 2, and 3 respectively at 98.86%; 96.21%; 99.62%, which is included in the very good criteria. (2) Relevant student’s activities that appear in the learning process in meetings 1, 2, and 3 respectively 96.30%; 98.52%; 97.78% and irrelevant activities that appear in meetings 1, 2 and 3 respectively 3.70%; 1.48%; 2.22%. (3) Students’ critical thinking skills increase from the results of the pretest to the posttest which is measured using the N-Gain Score formula, which is 100% of students complete in components of critical thinking, those are interpretation, analysis, inference, and explanation with the average gain score in the high category. (4) Students cognitive learning outcomes, show that 29 from 34 students completed or 85.29% and 5 students not completed or 14.71%. Keywords: Guided Inquiry, Reaction Rate, Critical Thinking Skills, Learning Outcomes